An Expert System Dataset for Checking the Potential for Administering a Covid-19 Vaccine in Indonesia: Forward-Chaining Inference Machine Approach - Rosyid Ridlo Al Hakim; Glagah E. Setyowisnu; Agung Pangestu (Journal of Global Engineering Research and Science, 2022)
Covid-19 has now spread extremely worldwide. World still fighting against Covid-19, as well as vaccination programs. The problem to get one of the existing vaccines, it is required first to carry out a vaccination eligibility screening test, then usually carried out with traditional form method by the healthcare staff. Seeing the development of an expert system that can be used as an alternative for health workers to help reduce the number of Covid-19 suppression so that it does not spread to health workers, because after all, someone who will vaccinate Covid-19 must be in good health, this is related to the pre-vaccination procedure. We proposed the expert system with forward-chaining method. The result is the dataset (rules collection) of an expert system based on a forward-chaining inference machine for administering all Covid-19 vaccines.